Вдосконалення креативної моделі особистості студента як перспективного фахівця - Фурманець, Борис Іванович; Грень, Лариса Миколаївна (Національний технічний університет "Харківський політехнічний інститут", 2019)
У статті аналізуються науково-концептуальні та методично-практичні аспекти щодо подальшого системного вдосконалення змісту креативної моделі особистості студента як перспективного фахівця. Контент-аналізом доведено, що побудова подібної моделі, відтворюється у ході навчально-виховного процесу ВТЗО з урахуванням визначених ознак майбутньої професійної діяльності певних фахівців. Саме ця тенденція, на думку науковців, найбільшою мірою обумовлює принципове врахування розвитку психолого-професійних особливостей, соціально-професійних якостей, комплексу показників характеристики особистості студента у тісному зв’язку з формуванням у нього соціально-гуманітарних та професійних знань, вмінь та якостей, що досить помітно впливають на зміст подібної моделі. Системно викладена науково-концептуальна та психологічно-професійна проблема вдосконалення змісту структури креативної моделі особистості студента – перспективного фахівця тісно поєднує у собі комплекс суттєвих складників з їх ідеально-змістовними критеріями. Подібна модель яскраво відбиває свою психологічно-професійну спрямованість на успішну творчо-ефективну діяльність певного фахівця.Усебічно обґрунтовані соціально – психологічні аспекти змісту креативної моделі особистості студента передбачають чітку організацію диференційованого моделювання ідеально-змістовних критеріїв, визначених складників цієї моделі в умовах навчально-виховного процесу ВТЗО та спеціально організованої психологічно-професійної практики. Креативна модель майбутнього спеціаліста, передусім, визначається найбільш суттєвими, соціально -психологічними та психологічно-професійно ознаками: здібністю до творчого і дивергентного мислення, інтересу до конструктивного та зразкового відтворення обов’язків фахівця, прийманням нетрадиційних рішень у практиці, зразковим виконанням студентських обов ’язків, породженням змістовних якостей, проявом оригінальних ідей і намірів, вдалим пристосуванням до умов перспективного фаху та ін. Викладений комплекс основних складників і критеріїв з креативними ознаками моделі має напрям свого подальшого контент -аналізу, головною метою якого є плідне формування психології особистості студента як перспективного фахівця, що відповідає сучасним освітнім вимогам.

The article contains analysis of scientific-conceptual and methodology-practical aspects concerning further systematic improvement of the content of personality creative model of a student as a perspective specialist. Content analysis proves that construction of such a model is reproduced in the course of training-and-education process at a higher technical education establishment with taking into account the defined qualities of future professional activities of specialists in certain professions. As scientists think, it is this model that stipulates to the largest extent important consideration of psychology-and-professional peculiarities’ development, social-and-professional qualities, a system of indicators characterizing a student’s personality in close connection with forming in them of social, humanities, and professional knowledge, skills, and qualities that affect the content of such a model quite considerably. Peculiarity and complexity of further solving the problem of further improvement of creativity model of a student’s personality as a perspective specialist at higher education establishments lies in the need of clear substantiation of its structure which would be exemplary and attractive for all interested specialists for its optimality combined with reliable and original construction. That is why primary attention is paid in the article to actual constructing of the structure of the model in question with analyzing the essence and integrity of its individual-psychologic, social-humanitarian, and psychologic-professional components with certain creativity criteria and qualities. The aim of the article is scientific-conceptual defining of the structure of creativity model of a student’s personality as a perspective specialist, its components by certain criteria, to detect their influence on a student’s psychology-professional forming; to compile a system of essential conditions, ways, and tasks of further more productive personality formation of a student in a certain speciality; relying on systematic and complex approach to specify scientific-conceptual definition of components and their criteria in relation to substantiating of the structure of the model in question characterizing a perspective specialist, dynamics and conditions of enhancing its creative reproduction at higher technical education establishments. In psychology-and-pedagogic science there has been formed an established opinion among psychologists-cum-educators that productive psychologyprofessional forming of perspective specialists in the course of training and education process is determined to the greatest extent by creating an original creativity model of a student’s personality as a perspective specialist [6, 9, 10]. The structural construct of such a model should reflect a close unity of essential socio-psychologic, humanitarian-professional, and motivation-creative components immediately connected with a complex of professional-and-practical traits, abilities, and creative skills. Social-and-psychologic aspects of the content of creativity model of a student’s personality suppose a clear organization of differential modelling of ideal-and-content criteria of determined components of this model under conditions of training-and-education process at a technical higher education institution and specifically organized psychology-and-professional practice. Socio-psychological and psychology-professional qualities of a perspective specialist’s creativity model are: ability of creative and divergent thinking, interest in constructive and exemplary reproduction of specialist duties, taking non-trivial decisions in practice, exemplary performance of student’s duties, shaping out one’s content traits, displaying original ideas and intentions, successful accommodation to conditions of chosen speciality, etc. The exposed complex of basic components and criteria with the model’s creativity markers is to be subjected to further content analysis, the main goal being fruitful forming the psychology of student’s personality as a perspective specialist in accordance with modern demands put forward to education.
Improvement of personality creativity model of a student as a perspective specialist
Keywords: модель особистості студентів; перспективні фахівці; креативна модель фахівців; критерії оцінки фахівців; ідеально-змістовні критерії; креативні показники; creativity model; model components; creativity indicators; attractive practices; professional evolvement